Deterministic loading of an individual atom：Towards scalable implementation of multi-qubit - 何军;刘贝;王杰英;刁文婷;靳刚;王军民 (Chinese physics B, 2017)
We report the realization of a deterministic single-atom preparation by the method of all-optical feedback. Using a fast-real-time feedback, the light-induced atom desorption effect and blue detuned light-induced atom collision process can increase a success probability of single-atom preparation up to more than 99%. We investigate the dynamics of loading single atom trapped in a trap with a size of hundreds of micrometers into a pair of microscopic tweezers. The detailed experimental results show that the feedback loading is spatially insensitive, which implies that it is possible to use the feedback protocol to simultaneously implement the loading of large number of qubits arrays.